2015
DOI: 10.5539/ijbm.v10n8p127
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Academic Climate and Individual Creativity on Lecturer Competence in Private University at Surabaya Indonesia

Abstract: This research aimed investigated the effect of simultaneous or partial academic climate and creativity lecturer on lecturer competence. Through purposive sampling, 72 tenured faculty who teach management studies courses responded to questions concerning academic climate (relationship, control capabilities and physical environment) and creativity (fluency, flexibility, originality, elaboration and redefinition) and competence (pedagogy, personal, professional, social). , and The results of the regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…Sosialisasi yang dilakukan mahasiswa Universitas Bhayangkara Surabaya di Dusun Gambir Anom adalah untuk memilah sampah organik yang digunakan untuk kompos serta sampah non organik untuk kerajinan yang bernilai ekonomis (Indrasari et al, 2015;Daniel Susilo et al, 2020).…”
Section: Gambar 1 Lokasi Kegiatanunclassified
“…Sosialisasi yang dilakukan mahasiswa Universitas Bhayangkara Surabaya di Dusun Gambir Anom adalah untuk memilah sampah organik yang digunakan untuk kompos serta sampah non organik untuk kerajinan yang bernilai ekonomis (Indrasari et al, 2015;Daniel Susilo et al, 2020).…”
Section: Gambar 1 Lokasi Kegiatanunclassified
“…So that good and bad academic atmosphere is closely related to the attitudes and behavior of the academic community, such as lecturers, students and university administrators. Meanwhile, according to Indrasari et al (2015), the academic atmosphere will also affect the competence of lecturers. In addition, , Yanti (2018), and Warka (2019) found that the academic atmosphere affected lecturer performance.…”
Section: Introductionmentioning
confidence: 99%
“…Organizational culture has a positive effect on performance (Indrasari, 2017); (Indrasari et al, 2018); (Indrasari et al, 2019). The academic climate also affects the competence of lecturers (Indrasari et al, 2015). Resource-Based Theory (RBT) explains that companies can gain a competitive advantage by owning, controlling and using strategic assets, including tangible assets and intangible assets (Wernerfelt, 1984).…”
Section: Introductionmentioning
confidence: 99%